Politicians and Power Structure in Samut Prakan Province - pirunnetre, krityanee (King Prajadhipok’s Institute Journal, 2020)
This article focuses the dynamic of influence of new and old political elite groups in the changing economic and social conditions in Samut Prakan Province. The study examines 1) economic and social changes in the Samut Prakan Province between 2538 (1995) and 2555 (2012); 2) the changes in the role of the traditional group of politicians in Samut Prakan Province; and 3) the relationship between the economic and social changes in Samut Prakan Province and the emergence of a new group of politicians. This study use descriptive analysis by focusing on documents and collecting data through in-depth interviews with members of the Assawaheam group and new politicians. The result of the study can be divided into three parts. In the first part, the study of the economic and social changes in Samut Prakan Province between 2538 (1995) and 2555 (2012) found that the economic and social conditions have developed continuously as indicated by the continuous rise in gross provincial product, the agricultural sector and industrial sector, the expansion of housing, and the increase in population. In the second part, the study focused the changing role of traditional politicians in the province. The findings showed that after Mr. Wattana Assawaheam, head of the Assawaheam group, lost the 2544 (2001) general election because of corruption cases related to the Klong Dan project, he to the subject land, Klong Dan, since 2544 (2001) make Mr. Wattana Assawaheam lost his political role in Samut Prakan. Although a political role in national politics of the Assawaheam Group is decreased, however, there were still has a role in the local politics. In the third part, the study focused on the relationship between economic and social changes in Samut Prakan Province and the emergence of new political groups. It was found that new political groups had a political role since the general election in 2544 (2001). This was because the economic and social changes also changed people’s ideas and concepts. People focused on political party policies that were expected to benefit the people. This brought caused high popularity for Thai Rak Thai Party. Thus it led to the emergence of a new political group in Samut Prakan Province.